Laïcité: A parallel French cultural policy (2002–2007). (August 2014) - Ahearne, Jeremy
The recasting of laïcité in France between 2002 and 2012 constituted a channel through which succeeding right-wing governments endeavoured to secure a form of cultural hegemony. This article focuses on the period 2002–7. The process leading to the anti-veil legislation of 2004 under President Chirac revealed how this symbolically charged motif once associated with the left had been displaced and integrated into a traditional and restrictive right-wing culture-shaping programme. Interior minister Sarkozy's endeavours between 2002 and 2004 to fashion an institutional dialogue with Islam in France were initially at odds with Chirac's programme. However, by 2007, Sarkozy had changed tack to produce an alternative reframing of laïcité, 'positively' celebrating the intertwining of national and Catholic cultures, whilst using Islam as a negative foil for the projection of that identity. This laid the groundwork for the subsequent hardening of laïcité debates and the appropriation of the term by the far right.